Modular simulation of neuroangiography and endovascular interventions in neuroradiology (Transactions on Additive Manufacturing Meets Medicine, 2021)
A concept for a specialized phantom system for the simulations of diagnostic and therapeutic procedures in neuroradiology is presented. The modular simulator can be used for testing and training of both, established and new approaches in image guided catheter interventions. The 3D printing of anatomical vessel phantoms allows for the reproduction of specific features of the vasculature on the path of the catheter.
Keywords: 3D-Printing; Vascular models Neuroradiology